Improving Employee Performance Through Training, Compensation, and Workload Distribution (A Literature Study) - Ahyauddin, Aa; Yosepha, Sri Yanthy (Dinasti Publisher, 2025)
The enhancement of employee performance has emerged as a primary focus within human resource management across various organisations. In this context, training, compensation, and workload distribution represent three key strategies that can significantly contribute to improving employee productivity and effectiveness. This research aims to explore how these three strategies can be effectively implemented to achieve optimal employee performance. The methodology employed in this study is qualitative, utilising a literature review approach that draws upon a range of relevant literature and case studies. Through meticulous identification and examination of previously conducted literature, it has been established that appropriate training, equitable compensation, and balanced workload distribution can significantly contribute to the enhancement of employee performance. It is anticipated that these findings will provide valuable insights for managers and organisational leaders in designing more effective strategies for employee performance development.